Review of Contemporary Irish Theatre: Histories and Theories, by Charlotte McIvor and Ian R. Walsh - Gloria García Pintueles (Review of Irish Studies in Europe, 2025)
Review of Contemporary Irish Theatre: Histories and Theories, by Charlotte McIvor and Ian R. Walsh (London: Palgrave Macmillan Cham, 2024), 352 pp., ISBN: 9783031550119, €41.50 (hardback)